Zero Waste Circular Economy: Transforming Chocolate Production into Chocolate Jam in Bali - Dwi Sihwinarti; Andreas James Darmawan; Anita Heptariza; I Made Satrya Ramayu; Kadek Nonik Erawati (Jurnal Ekonomi, 2024)
The  progress of the chocolate industry in Bali, as represented by Pod Chocolate Bali, offers tremendous potential for local economic contribution. However, the chocolate production process produces cocoa pulp as waste which can affect the environment and economic balance. This research discusses the implementation of the zero waste concept by integrating a circular economy through the use of cocoa pulp as a basic ingredient for producing chocolate jam. The background to this research illustrates the important role of chocolate in culture and the economy, but also highlights the challenges of waste generated during production. This research focuses on qualitative research methods with a case study approach that combines observation, interviews and document analysis. The research results show that implementing the zero waste concept by processing cocoa bean dregs into chocolate jam not only solves the waste problem, but also empowers local communities through training and skills development. Additionally, this initiative promotes a circular green economy by harnessing the full potential of cocoa beans. The spread of zero waste solutions in the Pod chocolate industry has had a positive impact in the form of improving the economy of chocolate SME in Bali. This strategy allows reducing food waste, increasing the added value of cocoa beans, and creating high-quality chocolate jam products that can meet local and international market demand. In this context, a zero waste solution not only makes the chocolate production process more sustainable, but also supports the development of cocoa cultivation which empowers local communities.